Percolação e Transição de Fase em Cerâmicas Supercondutoras - Amorim, Leandro Silva (2014)
This work tackles unusual features of superconductivity, more precisally two property that are little comprehended. The first one, which is the aim of this work, is the resistivity drop below the linearity of superconductors in the pseudogap phase. We believe the above critical temperature fluctuations overlap to form a path for the supercurrent, which will compete with the normal current in a parallel arrengement. These overlaps are studied using the statistical model of continnum percolation in a bidimensional network, formed by resistors, and the supercurrent path is caracterized as a infinite incipient cluster. The second subject to be considered is the double phase in Mercury perovskites, due to the Rhenium dopping. To approach to this problem we use the Ginzburg – Landau model for two coexisting order parameters.